Improving the Students’ Comprehension on Acid Natural Indicator through Discovery Learning - Nanik Utami (Universitas Sarjanawiyata Tamansiswa, 2022)
Teaching industrial chemical for students of vocational school in Indonesia is quite challenging due to the bulk materials in limited time. For Grade 10, the students should master the single and mixture substances into solutions. It means that they have to understand how to identify the acid and alkaline. In the laboratory, it is easy to recognize the acidity of a substance using litmus paper, pH meter or universal indicator. However, it would be tough if the students have to use natural indicator. By applying the classroom action research among students on grade 10 in one of vocational school in Yogyakarta, Indonesia, the current study attempts to increase the students’ competence in comprehending the use of natural indicator to measure the acidity. The discovery learning was chosen.